ARCTIC «UPGRADE» OF V. V. PUTIN, PRESIDENT OF THE RUSSIAN FEDERATION - I. S. Zonn (Проблемы постсоветского пространства, 2017)
After establishment of the Soviet power the Arctic for seven decades had been in the focus of attention accomplishing the heroic, repressive, “educational”, economic, political and ideological functions. In 1930-1950 General Secretary of the Central Committee of the Bolshevik Communist Party I.V. Stalin created the first Soviet Arctic shield that included the economic and military strategic power, transport targeted to protection of entirety and security of the Soviet country. The Stalin’s large-scale project of Arctic development was made public in 1931 and was targeted to the enhanced protection of the polar waters by establishing the naval base on the Barents Sea. For implementation of this project the White Sea-Baltic canal was constructed. The Trust “Arktikugol” was established on the Spitsbergen Archipelago to supply coal to the Northern Navy Fleet. The sea expedition over the Northern Sea Route was also organized to prove the possibility of shipping along this route for one navigation season. Upon its successful completion the Chief Department “Sevmorput” was set up here. The epoch of airship construction was opened to explore the Arctic air expanses. Later on there were expeditions to the North Pole, deployment of army on the Chukotka Peninsula, new expeditions to high latitude terrains, construction of high-capacity icebreakers, aerodromes and military bases on the coast of the Arctic Ocean. Unfortunately, in the 1990s in the time of the Soviet Union breakup and perestroika many facilities of the Stalin’s Arctic Shield had been lost and ceased to exist.The early 21st century witnessed the second energetic and goal-oriented breakthrough into the Arctic region and establishment of the second Arctic Shield or bastion based on the key principles of the Soviet Arctic Shield or, in other words, its upgrade in the new conditions of the polycentric world, which is justly connected with the name of Russian President Putin.The interest to the Arctic was revived after V.V. Putin was elected in 2000 the RF President and this was observed against the sharp changes in the political and economic situation in the country. The underlying stimuli were the opening of large offshore hydrocarbon fields in the Arctic seas and global climate warming. From this time on when the interest to the Arctic was on the rise again the attitude of the Russian president and government to this region had changed enormously. Putin personally keep in the focus of his attention all Arctic issues. One of the strategic goals of the policy formulated by Putin is apparently the revival of the Russian Arctic, creation of own Arctic Shield understanding quite clearly that this would require construction anew of the great part of the Arctic infrastructure. This publication investigates in detail the steps of V.V. Putin taken for development of the Arctic ways.